Physiological profiles of cortical responses to mechanical stimulation of the tooth in the rat: An optical imaging study. (1st September 2017) - Kaneko, Mari; Horinuki, Eri; Shimizu, Noriyoshi; Kobayashi, Masayuki
Highlights: Electrical and mechanical stimulation to the molar activates the cortex including S1, S2, and insular oral region (IOR). Electrical stimulation of the molar periodontal ligament (PDL) induced greater excitation in S2/IOR than S1. Mechanical stimulation induced greater or at least equivalent excitation in S1 compared to that in S2/IOR. Mechanical stimulation evoked excitation not only to the initial phase but also to the terminal phase of stimulation. Effective suppression of S2/IOR excitation by morphine suggests different roles for S1 and S2/IOR in pain processing. Abstract: The periodontal ligament (PDL) includes several types of nerve endings, such as Aβ-, Aδ-, and C-fibers, which play critical roles in detecting the strength and direction of occlusal force. Previous studies have demonstrated that electrical stimulation of the PDL activates the somatosensory and insular cortices. However, the profile of cortical excitation in response to mechanical PDL stimulation mostly remains unknown. To investigate the differences in cortical responses to electrical and mechanical stimulation of the maxillary first molar, we performed optical imaging to determine the responding cortical regions in combination with a pharmacological approach. The molar was mechanically stimulated by pulling in the rostral direction, and electrical stimulation was applied via bipolar electrodes inserted into the mesial PDL. Mechanical stimulation initially excited the primary somatosensory cortex (S1), whereas electrical stimulation evoked an initial response between the secondary somatosensory cortex (S2) and insular oral region (IOR). The characteristic feature responding to mechanical stimulation was the rebound response evoked at the end of mechanical stimulation. A longer mechanical stimulation evoked a larger amplitude of the rebound response. A paired-pulse protocol of mechanical stimulation revealed that the amplitude of the second response was smaller than the first response, in accordance with the shorter interstimulus interval. Systemic application of morphine, a potent blocker of nociception, reduced the amplitude of the maximum excitation, particularly in S2/IOR compared to S1. These results suggest that S1 and S2/IOR are principally excited by mechanical and electrical stimulation, respectively, and that S2/IOR is involved in nociception processing.